Perspectives on Virtual Museum Tours - Milena Jokanović (INSAM)
As a number of world museums have closed their doors for the public due to pandemic of the new Corona virus, curators are thinking of alternative ways of audience outreach: 3D virtual galleries are increasingly created, video guided tours shared, digitized collections put online. The new circumstances unquestionably bring potentials for growth, but carry numerous risks and inconsideration, as well. Many theoreticians argue that the crisis of this scale will undoubtedly fasten the digital transformation in museum and arts sector and consequently, in a much more wide sense influence the identity rethinking. However, the research of audience interest to virtual museum tours show there was a peak of just 3 days visiting these, massively followed by a fast decrease even the social isolation was globally still present and museum buildings still locked. Turning back to the genesis of the virtual museums, in the following paper, we will question why there is no interest to virtual museum content. Do tours answer the needs of the contemporary digital-born audience? Do these represent just a copy of settings from physical galleries or use potentials and logic of the new spaces? Will museums finally transform and enter into so many times nowadays mentioned digital shift answering the need of the new, transmedia perception of audience?